Determination of total arsenic and its species in rice by ICP-MS and HPLC-ICP-MS - Gueifão, Sandra (2012)
Ingestion of arsenic through food and water is the main path for this element to enter the human organism. Moreover, arsenic in general, and its chemical forms in particular, are well known to cause acute and chronic toxicity [1]. Hence, the determination of total arsenic is not sufficient to assess the risks since the toxicity of this element is highly dependent on its chemical form with inorganic arsenic; arsenite (AsIII) and arsenate (AsV); being more toxic than monomethylarsonic acid (MMA), dimethylarsinic acid (DMA) and Arsenobetaine (AsB). The determination of total arsenic and its species in rice is of special importance since rice forms a major dietary component for many populations. Also rice is included in many babyfoods. Since infants have low body weight they are more exposed to arsenic toxicity than adults. Therefore rice crops intended to be consumed by infants must be carefully monitored for arsenic content. Primarily, the present work was performed with the aim of determining total arsenic content in different varieties of rice samples. A total of 24 samples, from four different locations, were provided by a local manufacturer. Sample preparation included grinding and homogeneizing, followed by acid-assisted microwave digestion. Total arsenic determinations were performed by Inductively Coupled Plasma Mass Spectrometry (ICP-MS). Afterwards, two samples were chosen to develop a method for the determination of arsenic species. The technique used was High Performance Liquid Chromatography (HPLC) coupled to ICP-MS. The extraction, using a closed vessel microwave oven, was carried out with phosphoric acid. The chromatographic separation was achieved with an anionic exchange column (HAMILTON PRP-X100) which allowed detecting and quantifying four species (AsB, DMA, AsIII, AsV). The mobile phase was chosen based on scientific literature and adjusted to laboratory conditions. The obtained results showed that the concentration of arsenic in rice ranged between 115µg/kg and 611µg/kg. No apparent relation exists between variety, location and arsenic content. Regarding the speciation study results showed that in these samples 80% of arsenic was present as DMA and 20% as inorganic arsenic. [1] S. D’Ilio, M. Alessandrelli, R. Cresti, G. Forte, S. Caroli, Microchemical Journal, 2002, 73, 195-201.